Intellectual Degradation Amidst the Development of AI Technology: A Comparison Between AI Dependency Students and AI Assisted Learning Students - Ahmad Choirun Najib; Darnoto Darnoto (Pascasarjana Universitas KH. Abdul Chalim, 2026)
This study aims to compare the trends in Artificial Intelligence (AI) usage patterns among students of the Islamic Religious Education (PAI) Study Program at Nahdlatul Ulama Islamic University, Jepara, namely AI Dependency and AI Assisted Learning. These trends are determined based on the patterns of AI use in academic activities, including the use of AI without editing, the use of AI in writing scientific articles without filtering, the use of AI as a framework for assignments, reference searches through AI, and information verification using official scientific sources. The study used a comparative quantitative approach with a survey design of 84 PAI students. Data were collected through an online questionnaire and analyzed descriptively-comparatively using frequency distribution and percentages. The results showed that 98.8% of respondents acknowledged that AI helped complete academic assignments and 95.2% felt an increase in learning efficiency. However, only 10.7% of respondents used AI completely without editing, while 81% stated that excessive use of AI has the potential to reduce critical thinking skills and academic integrity. In addition, 63.1% of respondents used AI to obtain initial references, while 79.8% continued to verify information through scientific indexing pages. These findings indicate that Islamic Religious Education students are more likely to adopt AI-assisted learning patterns than AI-dependency, utilizing AI as a learning support tool, not a substitute for thinking. This research underscores the importance of strengthening AI literacy and ethical guidelines for AI use in Islamic higher education.